The role of school accreditation in improving educational quality - Tri Ananda Setiyani; Nur Adzkia Kamilah; Resyadilla Azkia; Putri Medina Heru Arnafama; Siti Raisyah; Aslamiah Aslamiah; Celia Cinantya (Universitas Pendidikan Indonesia, 2025)
School accreditation has often been understood as merely an assessment and administrative fulfillment mechanism, resulting in its suboptimal contribution to improving educational quality. This situation requires implementing a quality management approach to strengthen the role of accreditation as an instrument for continuous improvement. This study aims to analyze the relationship between school accreditation and educational quality by applying Total Quality Management (TQM) principles in three A-accredited public junior high schools in Banjarmasin City. The study used a qualitative approach with a case study design. Data were collected through semi-structured interviews, observations, and a review of accreditation documents. The results indicate that accreditation serves not only as an external evaluation but also encourages facility improvements, strengthens the learning process, and improves student achievement when integrated with the principles of continuous improvement and stakeholder involvement, as in TQM. However, the implementation of this integration still faces obstacles, including limited funding, resistance from some teachers, and disparities in facilities and infrastructure. Strengthening the link between accreditation and TQM could serve as a model for sustainable educational quality assurance. Abstrak Akreditasi sekolah selama ini kerap dipahami sebatas mekanisme penilaian dan pemenuhan administrasi, sehingga kontribusinya terhadap peningkatan mutu pendidikan belum optimal. Kondisi ini menuntut penerapan pendekatan manajemen mutu yang mampu menguatkan peran akreditasi sebagai instrumen perbaikan berkelanjutan. Penelitian ini bertujuan menganalisis keterkaitan antara akreditasi sekolah dan mutu pendidikan melalui penerapan prinsip Total Quality Management (TQM) pada tiga SMP Negeri terakreditasi A di Kota Banjarmasin. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara semi-terstruktur, observasi, serta telaah dokumen akreditasi. Hasil penelitian menunjukkan bahwa akreditasi berperan tidak hanya sebagai evaluasi eksternal, tetapi juga mendorong perbaikan fasilitas, penguatan proses pembelajaran, dan peningkatan prestasi murid ketika diintegrasikan dengan prinsip perbaikan berkelanjutan dan keterlibatan seluruh pemangku kepentingan sebagaimana dalam TQM. Namun, implementasi integrasi tersebut masih menghadapi kendala berupa keterbatasan pendanaan, resistensi sebagian guru, serta ketimpangan sarana dan prasarana. Penguatan keterkaitan antara akreditasi dan TQM berpotensi menjadi model penjaminan mutu pendidikan yang berkelanjutan. Kata Kunci: akreditasi sekolah; mutu pendidikan; Total Quality Management; TQM